A new procedure for solving linear programming problems in an intuitionistic fuzzy environment - Malathi, C; Umadevi, P (Journal of physics. Conference series, 2018)
This paper presents a novel approach for solving Linear Programming Problems in an Intuitionistic Fuzzy environment. Here, the cost coefficients in the objective function of an Intuitionistic Fuzzy Number Linear Programming Problem (IFNLPP) are considered to be Symmetric Triangular Intuitionistic Fuzzy Numbers (STriIFNs) and the problem has been solved without converting them to crisp Linear Programming Problem using linear Ranking function. Intuitionistic Fuzzy Simplex algorithm which is a most powerful tool of handling any IFLPP has been used for solution procedure. An example has also been illustrated to reveal the effectiveness of the projected method.